Pelatihan Teknik Penyusunan Studi Literatur Menggunakan VOSViewer dan Teknik Sitasi Menggunakan Zotero - Etty Gurendrawati; Dwi Kismayanti Respati; Gentiga Muhammad Zairin; Suherman; Suparno; Indra Pahala; Agus Wibowo; Rr. Ponco Dewi Karyaningsih; Tri Hesti Utaminingtyas; Tya Sisti Widyastuti (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
Publication is one of the tridharma of higher education that can demonstrate the achievements of lecturers and enrich knowledge. However, many students still face difficulties in writing high-quality scientific papers and publishing them in national and international journals. To address this issue, the author conducted training using VOSviewer and Zotero applications to assist students in writing and publishing scientific papers. The results of the training showed an improvement in participants' knowledge and skills, and the participants expressed satisfaction with the success of the program. In conclusion, this training effectively enhances students' knowledge and motivation to publish their scientific work, and it is hoped that such activities can be conducted regularly to increase the number of student publications in reputable journals.